2016
DOI: 10.3892/ol.2016.4454
|View full text |Cite
|
Sign up to set email alerts
|

Bellini's duct carcinoma: A report of two cases and a review of the literature

Abstract: Abstract. Bellini's duct carcinoma (BDC) is a rare and aggressive variant of renal cell carcinoma that possesses an extremely poor prognosis. The greater the grade or stage of disease, the poorer the prognosis tends to be. This study presents two cases of BDC; one case of low grade BDC and one case of high grade BDC in a 47-year-old male and 74-year-old female, respectively. The 47-year-old male patient presented with painless gross hematuria, which had lasted for 3 weeks and subsequently underwent purely lapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…Laboratory studies are usually normal, though microscopic hematuria and mild anemia were reported in some cases [2,5,6]. Alpha-fetoprotein (AFP), cancer embryonal antigen (CEA), and urine cytology might be positive [6] and, in some cases, such as ours, an important clue for a definite diagnosis.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Laboratory studies are usually normal, though microscopic hematuria and mild anemia were reported in some cases [2,5,6]. Alpha-fetoprotein (AFP), cancer embryonal antigen (CEA), and urine cytology might be positive [6] and, in some cases, such as ours, an important clue for a definite diagnosis.…”
Section: Discussionmentioning
confidence: 80%
“…In addition to the collecting duct mass, our patient showed multiple infracentimetric perihilar lymph nodes, hence considered a locally advanced disease. Heterogeneous masses, irregular borders, variable echoes, and blood flow signals were described on ultrasonography [2,6]. MRI reveals an isointense image on T1, iso-or hypointense image on T2, and lower enhancement compared to the normal cortex and medulla [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los factores que determinan un mejor pronóstico de estos tumores son el bajo grado y un menor estadio tumoral [14][15][16] . Existen pocos casos de este tumor con crecimiento exofítico y afectación linfática 6,8,9,17 y escasos estudios que describan el diagnóstico radiológico y su diagnóstico diferencial.…”
Section: Discussionunclassified
“…el túbulo contorneado proximal 6 . Mancilla-Jiménez et al 7 en 1976 describieron por primera vez la existencia de algunos carcinomas papilares que provenían de los túbulos colectores.…”
unclassified